1986
DOI: 10.21273/jashs.111.2.311
|View full text |Cite
|
Sign up to set email alerts
|

High-density Nursery System for Breeding Peach and Nectarine: A 10-year Analysis

Abstract: A 10-year analysis of the high-density nursery (HDN) in the breeding of low-chilling peach and nectarine [Prunus persica (L.) Batsch] cultivars indicated selection was effective during the first cropping year for chilling requirement, fruit development period, size, color, shape and firmness but not for crop load, which needs to be evaluated at normal spacing over several years. The HDN system effectively has advanced the breeding program by promoting short generation time, reducing labor and space, and allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The highest chilling requirement clones ceased growth first in the presence of shortening days. A correlation matrix among chilling requirement, length of fruit development period, crop load, fruit color, fruit size, fruit shape, and fruit firmness showed a few low, but significant relationships (15). None of the correlations were high enough to be of use in seedling selection.…”
Section: Relationship Of Charactersmentioning
confidence: 95%
See 3 more Smart Citations
“…The highest chilling requirement clones ceased growth first in the presence of shortening days. A correlation matrix among chilling requirement, length of fruit development period, crop load, fruit color, fruit size, fruit shape, and fruit firmness showed a few low, but significant relationships (15). None of the correlations were high enough to be of use in seedling selection.…”
Section: Relationship Of Charactersmentioning
confidence: 95%
“…This relationship must be close enough for high genetic progress to be made in advancing potential commercial selections. Recent stud ies have shown that expression of traits in the fruiting nursery, such as chilling requirement, fruit development period, fruit size, and flower bud set is highly correlated with expression in mature clones of the same selections in simulated commercial plantings (15). Chilling requirement was slightly higher and fruit size slightly lower in young seedlings selections in the fruiting nursery than in mature trees of the sam e selections in sim ulated com m ercial plantings.…”
Section: Relationship Of Charactersmentioning
confidence: 98%
See 2 more Smart Citations